Corticosteroide antenatal e prematuridade: análise do pré-natal, parto e desfechos neonatais de pacientes atendidos no Hospital Universitário de Santa Maria - Pes, Fernanda Bressan (2023)
Currently, the prevalence of prematurity has been increasing worldwide, with Brazil ranking ninth among the 10 countries with the highest rates, around 11.2 per 100 live births (Dias BAS et al.,2022). Prematurity is the main cause of morbidity and mortality in the neonatal period (ALBUQUERQUE et al., 2002). Among its consequences are a series of disorders in the newborn, such as increased risk of infections, intracranial and periventricular hemorrhage, jaundice, retinopathy and especially respiratory difficulties (PACHI, 2003). The difficulty of early diagnosis of preterm labor is recognized, so the prevention of complications in these fetuses becomes a priority during prenatal care. In this context, the use of corticoids emerges with the intention of reducing neonatal mortality rates by stimulating fetal lung maturation (MENEGUEL et al.,2022). Thus, the aim of this study is to analyze in patients seen at the Santa Maria University Hospital whether the administration of corticoids was well indicated, by reviewing the context of medication administration, the risk factors for prematurity related to pregnancy and the expected outcomes for these patients and fetuses. Methodology: a cross-sectional analysis was performed by collecting data from medical records of pregnant women who underwent corticoid during care or hospitalization at the obstetric center of the University Hospital of Santa Maria from January to December 2019. For the characterization of the sample, a descriptive analysis of the data of the parturients and newborns was performed, and the categorical variables were presented as percentages and quantitative variables as means and standard deviations. In the qualitative variables analysis, the association was verified through the chi-square test and in the quantitative variables the z test of two samples. The associations were considered significant when the results had a p-value < 0.05. Results: there was a significant difference in the proportion of preterm NB (66.3%) whose mothers used corticoids, corresponding to the majority of cases, compared to nonpremature infants (33.7%) (p=0.003). Regarding 7-day birth, a statistical association with prematurity can be observed, i.e., most patients who were delivered within 7 days actually had premature fetuses. (p< 0,001). The percentage of patients who had premature fetuses and delivered within 7 days was 46.9 %, the most prevalent maternal pathologies in the patients were hypertensive disorders and diabetes. There was a prevalence of premature fetuses in patients with pathologies (89.1%). Maternal pathologies were also prevalent in mothers of fetuses born at term (75%). Conclusion: most of the patients studied had corticoids administered according to the current indication in the literature, considering that most had preterm births within seven days of medication administration.